ATMPH 2020
DOI: 10.36295/asro.2020.23228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ZnO NPS on Streptococcus pyogenes in vivo

Abstract: In vivo study revealed that ZnO nanoparticles treatment of Streptococcus SPP contaminated injured skin showed good prognosis and good healing process include complete regeneration of the epithelial cells of the epidermis and increase of cellulartiy of the dermal content compared with untreated group.In conclusion, treatment of S. pyogenes infected skin with Zinc oxide nanoparticles concentration (2 mg/ml) limit the skin damage and localized the lesion to the incision site with good healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Subsequently, although the use of aseptic surgical procedures and hospital-acquired infections related to implants still result in major morbidity and mortality rate [2]. Multidrug resistance pathogenic bio lm infections causing important problem in wold new alternatives to antibiotic therapy which can effectively Noval metal nanoparticles (NPs) have gained signi cant interest in the eld of medical treatment and wide range of applications [3]. CuoNPs show antibacterial, antioxidant with cytotoxicity and different applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, although the use of aseptic surgical procedures and hospital-acquired infections related to implants still result in major morbidity and mortality rate [2]. Multidrug resistance pathogenic bio lm infections causing important problem in wold new alternatives to antibiotic therapy which can effectively Noval metal nanoparticles (NPs) have gained signi cant interest in the eld of medical treatment and wide range of applications [3]. CuoNPs show antibacterial, antioxidant with cytotoxicity and different applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…or resistant (R) to a particular drug by comparison with the standard inhibition zone (Table 1). [14,15].…”
Section: Antibiotic Resistance Testmentioning
confidence: 99%
“…It has been shown that various NMs, such as polymeric or hybrid NMs, gold and magnetic nanoparticles (NPs) respond to stimuli from the external resulting in temporally regulated macromolecule release. For these reasons, synthetic NMs have been thoroughly studied and applied in pharmacology and medicine over the past 20 years, especially for diagnostic and therapeutic purposes [1]. Copper (Cu) nanoparticles are the ideal among all metal nanoparticles because of their distinctive chemical and physical characteristics, including excellent thermal conductivity, electrical conductivity and biological activity [2].…”
Section: Introductionmentioning
confidence: 99%